Evaluate the use of farmlands encumbered with electric grid facilities: damage factors and solution approaches - Murasheva, Alla A.; Stolyarov, Viktor M.; Lomakin, Gennadiy V.; Lepekhin, Pavel A.; Tarbaev, Vladimir A. (Opción, 2019)
This article presents solution approaches towards the effective use of farmlands encumbered with electric grid facilities. This problem is characterized not only by the difficulties in the process of land cultivation, but also by other damage factors affecting this process, as well as yields, tax and rent losses. The choice of methods for assessing the negative processes is regarded as one of the major problems when it comes to placing electric grid facilities. The use of economic tools in assessing damage and finding the most profitable way to use farmlands for placing and running electric grid facilities was substantiated.